Complex Cerebrovascular Presentation in Central Nepal with Therapeutic Challenge - Karki, Karuna T; Chaudhary, Pramod K; Bhattarai, Binod; Munakomi, Sunil (Nepal Journal of Neuroscience, 2016)
Effective management of complex vascular malformation remains one of the more challenging problems faced in most of the developing countries where modern therapeutic resources are deficient. Giant arteriovenous malformations and other vascular malformation like dural arteriovenous malformations are often associated with higher morbidity and mortality rates. These lesions are considered as untreatable or inoperable. Endovascular therapy is an expanding science for managing complex vascular malformations in Nepal that has many constraints. This outset will have positive impact in the country that has to deal with moderate resources to provide wide therapeutic benefit. Here we present our preliminary experience about the use of ethylene vinyl alcohol (Onyx- 18) to embolize dural arteriovenous fistula and use of n-butyl cyanoacrylate to embolize giant supratentorial arteriovenous malformation. Nepal Journal of Neuroscience 12:73-80, 2015